Given: The angles as shown in the image
![\begin{gathered} m\angle DEY=105^0 \\ m\angle DEF=27x+3 \\ m\angle YEF=6x+3 \end{gathered}]()
To Determine: The measure of angle DEF
Solution
It can be observed that
![\begin{gathered} m\angle DEY+m\angle YEF=m\angle DEF \\ Therefore \end{gathered}]()
![\begin{gathered} 105^0+6x+3=27x+3 \\ 105=27x-6x+3-3 \\ 105=21x \\ x=(105)/(21) \\ x=5 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/z3pgmmg9kc3f6no8vrlz785y0vdr7d6mnj.png)
![\begin{gathered} m\angle DEF=21x+3 \\ =21(5)+3 \\ =105+3 \\ =108 \end{gathered}]()
Question 12
Given:
![\begin{gathered} m\angle UIJ=x+43 \\ m\angle HIJ=66 \\ m\angle HIU=x+37 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/dq901k7iena8d24fx8t72hgxh6tz53nzuy.png)
To Determine: The measure of angle HIU
Solution:
It can be observed that
![m\angle UIJ+m\angle HIU=m\angle HIJ](https://img.qammunity.org/2023/formulas/mathematics/college/mtlsakmfvf0whkzzgdzcos183b9am5ybsd.png)
![\begin{gathered} x+43+x+37=66^0 \\ Collect-like-terms \\ x+x+43^0+37^0=66^0 \\ 2x+80^0=66^0 \\ 2x=66^0-80^0 \\ 2x=-14^0 \\ x=-(14^0)/(2) \\ x=-7^0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/vnyl4ubmltkot0zh1ayh2rwgsga0tzekpe.png)
Therefore, the measure of angle HIU would be
![\begin{gathered} m\angle HIU=x+37^0 \\ m\angle HIU=-7+37^0 \\ m\angle HIU=30^0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/9jjxs4vwpw4vkhr5a9kapu31mj9zi74yjf.png)
Hence, the measure of angle HIU is 30⁰